Wind Pollination in Indian Mustard [Brassica juncea (L.) Czern & Coss] - N.C. SINGHAL; K.S. MANKAR; J.B.YADAV; ASHOK GAUR (Seed Research, 2026)
The experiments to assess the extent of wind pollination in Brassica juncen ev. Pusa Bold were conducted at IARI, New Delhi for three years (1996-97-1998-99). Dispersal of pollen grains by wind was noticed up to 35 meters from the pollen source. Air-borne pollen grains may pass through insect proof net and the effective pollination may occur. The extent of wind pollination was recorded up to 11 to 17.5 per cent. In want of pollen the flowers of male sterile plants may develop multistigmas to intercept effectively wind-borne pollen.